[1, 10]Phenanthroline based cyanine dyes as fluorescent probes for ribonucleic acids in live cells. (23rd October 2017) - Kovalska, Vladyslava; Kuperman, Marina; Varzatskii, Oleg; Kryvorotenko, Dmytro; Kinski, Elisa; Schikora, Margot; Janko, Christina; Alexiou, Christoph; Yarmoluk, Sergiy; Mokhir, Andriy
Abstract: A series of monomethine, trimethine- and styrylcyanine dyes based on a [1, 10]phenanthroline moiety was synthesized, characterized and investigated as potential fluorescent probes for nucleic acids in cell free settings and in cells. The dyes were found to be weakly fluorescent in the unbound state, whereas upon the binding to dsDNA or RNA their emission intensity raised up to 50 times (for monomethine benzothiazole derivativeFT1 complexed with RNA). The strongest fluorescence intensity in assemblies with dsDNA and RNA was observed for the trimethine benzothiazole derivativeFT4 . The quantum yield ofFT4 fluorescence in its complex with dsDNA was found to be 1.5% and the binding constant ( K b ) was estimated to be 7.9 × 10 4 M −1 that is a typical value for intercalating molecules. TheFT4 dye was found to be cell membrane permeable. It stains RNA rich components—the nucleoli and most probably the cytoplasmic RNA.FT4 bound to RNAs delivers a very strong fluorescence signal, which makes this easily accessible dye a potentially useful alternative to known RNA stains, e.g. expensive SYTO ® 83. The advantage ofFT4 is its easy synthetic access including no chromatographic purification steps, which will be reflected in its substantially lower price.